Esterifikasi dan Transesterifikasi Minyak Kelapa Sawit Off-grade Menjadi Biodiesel Menggunakan Katalis Barium Hidroksida - Nurfatihayati; Helwani, Zuchra; Bahri, Syaiful (Talenta Publisher (Universitas Sumatera Utara), 2025)
This research aimed to produce biodiesel from off-grade palm oil using barium hydroxide (Ba(OH)2) catalyst. The free fatty acid (FFA) content in off-grade palm oil is quite high, so the biodiesel production process is carried out in two-stages, i.e. esterification and transesterification. The esterification of off-grade palm oil (500 mL) was carried out at 60 oC for 1 hour, methanol:oil molar ratio of 12:1, stirrer speed of 400 rpm, and 1 wt-% sulfuric acid (H2SO4) as the catalyst. Next, the transesterification process used a methanol:oil molar ratio of 9:1, stirrer speed of 400 rpm, for 2 hours with the variation of temperatures (50, 60, and 70 oC) and Ba(OH)2 catalyst amounts (1, 2 and 3 wt-%). The best result was obtained with 60 oC and Ba(OH)2 catalyst amount 3 wt-%. Based on Gas Chromatography-Mass Spectroscopy (GC-MS) analysis, the best yield of fatty acid methyl ester was 98.97%, with major components being 40.87% palmitic acid and 35.87% oleic acid. The characteristics of biodiesel produced were density of 860.46 kg/m3, viscosity of 4.08 mm/s2, flash point of 145 oC and acid value of 0.457 mg KOH/g biodiesel.